Clinical MRI of the Abdomen Why,How,When - Gourtsoyiannis, Nicholas C.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This volume, which explains why, when, and how abdominal MRI should be used, focuses in particular on the most recent developments in the field. After introductory chapters on technical considerations, protocol optimization, and contrast agents, MRI of the various solid and hollow viscera of the abdomen is addressed in a series of detailed chapters. Relevant clinical information is provided, and state of the art protocols presented. With the help of numerous high-quality illustrations, normal, variant, and abnormal imaging findings are described and potential artefacts highlighted. Differential diagnosis is given extensive consideration, and comparisons are made with competing methodologies when relevant. Each of the chapters is rounded off by a section on "pearls and pitfalls". The closing chapters focus on findings in the pediatric abdomen, advances in MRI specifically relevant to cancer patients, and the use of abdominal MRI at 3 Tesla. This book, written by leading experts, will be of value to all who are involved in learning, performing, interpreting, and reporting abdominal MRI examinations.
From the contents: Technical Considerations and Protocol Optimization -- Contrast Agents -- Liver and Biliary Tract.-Pancreas.-Splee -- Adrenals.-Kidneys.-Gut.-Pelvis -- Pediatric Abdomen -- MRI Advances in Patients with Cancer -- Abdominal MRI at 3 Tesla.
Keywords: Medicine; Radiology, Medical; Internal medicine; Gastroenterology; Abdomen -- Surgery; Medicine & Public Health; Imaging / Radiology; Gastroenterology; Internal Medicine; Abdominal Surgery